La motivación en los niños y niñas de sexto y séptimo año de educación general básica durante el desarrollo de las clases de cultura física de la escuela fiscal mixta Zulima Vaca Rivera del cantón Pasaje en el periodo lectivo 2013 – 2014. - Marín Apolo, Nubia Yadira (2015)
Motivation is considered education as one of the main intermediaries for effective development of teaching and learning processes, one of the primary reasons for conducting this research is to help solve different educational problems living daily population student of the Joint Public School Zulima Vaca Rivera also want to highlight the importance of teacher preparation for this qualified impart their knowledge appropriately and enable the development of skills in students.